2010
DOI: 10.18632/oncotarget.164
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipids in invadopodia and podosomes: Key structures for cancer invasion and metastasis

Abstract: AbstrAct:Invadopodia are extracellular matrix (ECM)-degrading protrusions formed by invasive cancer cells. Podosomes are structures functionally similar to invadopodia that are found in oncogene-transformed fibroblasts and monocyte-derived cells, including macrophages and osteoclasts. These structures are thought to play important roles in the pericellular remodeling of ECM during cancer invasion and metastasis. Much effort has been directed toward identification of the molecular components and regulators of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…Significantly, we found that MUC1 and CIN85 co-localize at invadopodia-like protrusions. As the invasive capacity of cancer cells depends in part on their ability to assemble invadopodia [3235], the formation of the MUC1/CIN85 complex may be a requirement for this process. We show that MUC1 and CIN85 co-localize with two known invadopodial proteins, cortactin and MT1-MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, we found that MUC1 and CIN85 co-localize at invadopodia-like protrusions. As the invasive capacity of cancer cells depends in part on their ability to assemble invadopodia [3235], the formation of the MUC1/CIN85 complex may be a requirement for this process. We show that MUC1 and CIN85 co-localize with two known invadopodial proteins, cortactin and MT1-MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Arp2 and Arp3 expression in cancer cells was cytoplasmic as has been previously described [12] Both proteins were co-expressed in 78 cases (88.6%) and the statistical significant correlation between Arp2 and Arp3 expression seen in positive cases suggests formation of the Arp2/3 complex in those cells [12] [13] [15]. Formation of Arp2/3 complex is a prerequisite for the neoplastic cells to form filopodia, lamellipodia and invadopodia and acquire motility [4] [5] [22] and cells that express the Arp2/3 complex have greater ability for tissue movement [8] [22] [23] [24] [25]. Similar expression of Arp2/3 complex has been reported in gastric, colorectal, breast, lung, pancreatic and liver metastasis from colon carcinomas, as well as in gliomas [12]- [18].…”
Section: Discussionmentioning
confidence: 83%
“…Although podosomes may play an important role in matrix remodeling during cancer metastasis, the mechanism of podosomes assembly is still unknown. 39 Microvascular endothelial cells can form podosomes without specific stimulation. 6 Nck1 has been implicated in invadopodia formation and matrix degradation in various tumor cells, including breast carcinoma and melanoma cells.…”
Section: Nck Adaptors Play An Essential Role In Podosome-mediated Mmentioning
confidence: 99%